11-9x=79-37

Simple and best practice solution for 11-9x=79-37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-9x=79-37 equation:


Simplifying
11 + -9x = 79 + -37

Combine like terms: 79 + -37 = 42
11 + -9x = 42

Solving
11 + -9x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -9x = 42 + -11

Combine like terms: 11 + -11 = 0
0 + -9x = 42 + -11
-9x = 42 + -11

Combine like terms: 42 + -11 = 31
-9x = 31

Divide each side by '-9'.
x = -3.444444444

Simplifying
x = -3.444444444

See similar equations:

| (-4u^2+2u+3)+(8u^2-2u-5)-(-u^2+9u+8)= | | 12.3=0.41 | | -(8-9a)-(25+8a)-8=-(6-7a)+(-a)+5 | | 22x+2=10+74 | | 5=n/8 | | 384=12(-8+5a) | | 7y+2y=35 | | 96-4x=32x+20 | | 6+4h=30 | | (9u^2-9u-6)+(-5u^2+4u+8)-(-7u^2+9u+7)= | | 11=x*5 | | -7-5x=5x+8 | | (16/7)/(8/35) | | 5x+2x-9= | | 96-4x=32+20 | | 16/7/8/35 | | 5x+11=67-3 | | In(x+3)-In(x-1)-In(x+2)+In(x+3)=0 | | 3+f/3=10 | | 2x/3+1.5x=16-x/2 | | y^2+14y+24= | | 8-2(-2)y=24 | | 8-2x-2=24 | | 10[z-(10z+14)+5]=3z+3 | | 4x-2=3(x+4) | | 2.3x+59.4=24.3-9.4x | | 5u+3=18+u | | x+14=62 | | z^2+6z-16= | | r/3-4 | | x^2+7x+xy+16y^2= | | e/10-4=-6 |

Equations solver categories